Pengaruh Strategi Green Marketing Terhadap Kinerja Keuangan Dan Non-Keuangan Perusahaan - Yuni Adinda Putri; Rifani Akbar Sulbahri; Gumulya Sonny Marcel Kusuma (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
This study aims to present a reflection of the literature on green marketing strategies and analyze seven factors that will affect company performance. This research refers to the literature review method. As green marketing strategies become increasingly important for companies following the triple bottom line performance evaluation, this research seeks to better understand the role of the